An all-arthroscopic light bulb technique to treat osteonecrosis of the femoral head through outside-in fashion without distraction: A case report - Xiong, Hua-zhang; Deng, Yu-hong; Jin, Ying; Wang, An-hong; Hong, Song (Frontiers in Surgery, 2022)
The technique of distraction has been widely used in hip arthroscopy for opening joint spaces. However, an all-arthroscopic light bulb technique through outside-in fashion without distraction has not been reported for the treatment of osteonecrosis of the femoral head (ONFH). A 29-year-old man was admitted to our department with hip pain and limited range of motion (ROM) in both hips over 4 months. X-rays, computed tomography (CT), and magnetic resonance imaging (MRI) showed a mixed appearance, including sclerosis and cysts on the anterosuperior site of the bilateral femoral heads. The patient had an 11-year history of liquor intake. In addition, no other pathologies were found before the operation. After diagnosing bilateral ONFH (stage II) according to the Ficat classification, the patient underwent an all-arthroscopic light bulb technique through outside-in fashion without distraction because of failing conservative treatment. At the 2-year postoperative follow-up, the patient had neither pain nor limitation of ROM. The postoperative x-ray, CT, and MRI revealed a well-healed area of the previous bone grafting in the bilateral femoral heads. An all-arthroscopic light bulb technique through outside-in fashion without distraction can be a feasible method for the treatment of early-stage ONFH. This case reminds us that distraction- and perforation-related complications may be avoided in patients with ONFH without the concomitant pathologies of the central compartment.